Initial subjective reward: single-exposure conditioned place preference to alcohol in mice - Grisel, Judith E.; Beasley, John B.; Bertram, Emma C.; Decker, Brooke E.; Duan, Chunyu A.; Etuma, Mahder; Hand, Annie; Locklear, Mallory N.; Whitmire, Matthew P. (Frontiers in Neuroscience, 2014)
Most adults consume alcohol with relative impunity, but about 10-20% of users persist (or progress) in their consumption, despite mounting and serious repercussions. Identifying at-risk individuals before neuroadaptative changes associated with chronic use become well ingrained is thus a key step in mitigating and preventing the end stage disease and its devastating impacts. Explaining liability has been impeded, in part, by the absence of animal models for assessing initial sensitivity to the drug’s reinforcing properties, an important endophenotype in the trajectory toward excessive drinking. Here we assess the initial rewarding effects of the drug in a novel application of the conditioned place preference paradigm. In contrast to previous studies that have all employed repeated drug administration, we demonstrated a robust preference for a context paired with a single exposure to 1.5g/kg EtOH in male and female subjects of three strains. This model validates an assay of initial sensitivity to the subjective rewarding effects of alcohol, a widely used drug with multifarious impacts on both brain and society, and provides a new tool for theory-driven endophenotypic pharmacogenetic approaches to understanding and treating addiction.